2006
DOI: 10.1097/01.ccm.0000201004.30750.d1
|View full text |Cite
|
Sign up to set email alerts
|

L-alanyl-L-glutamine dipeptide–supplemented total parenteral nutrition reduces infectious complications and glucose intolerance in critically ill patients: The French controlled, randomized, double-blind, multicenter study*

Abstract: TPN supplemented with Ala-Gln dipeptide in ICU patients is associated with a reduced rate of infectious complications and better metabolic tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
126
3
17

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(154 citation statements)
references
References 44 publications
(62 reference statements)
8
126
3
17
Order By: Relevance
“…24 We found that GLN supplementation in the nonpancreatic surgical cohort significantly decreased (by an average of 12 days) the number of days patients required mechanical ventilation, probably because of the reduced incidence of pneumonia. Dechelotte et al 42 recently demonstrated a significant decrease in the incidence of pneumonia and the average number of infections per patient with GLN-PN in a mixed medical/surgical patient population in 16 French ICUs. Larger trials that are powered to test the hypothesis that GLN-supplemented PN decreases ARDS and overall hospital mortality rates are needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 We found that GLN supplementation in the nonpancreatic surgical cohort significantly decreased (by an average of 12 days) the number of days patients required mechanical ventilation, probably because of the reduced incidence of pneumonia. Dechelotte et al 42 recently demonstrated a significant decrease in the incidence of pneumonia and the average number of infections per patient with GLN-PN in a mixed medical/surgical patient population in 16 French ICUs. Larger trials that are powered to test the hypothesis that GLN-supplemented PN decreases ARDS and overall hospital mortality rates are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Several controlled trials in specific subgroups of postsurgical and other types of patients have shown beneficial clinical or metabolic effects when GLN is added to PN. 25,[31][32][33][34][35]39,41,42 These studies have incorporated L-GLN doses in PN ranging from 0.29 to 0.57 g/kg/d, 25,[31][32][33][34][35]39 and alanyl-GLN dipeptide doses similar to the dose used in the current trial (0.40-0.50 g/kg/d or equivalent to 0.26-0.33 g of L-GLN/kg/d). However, several trials also show no benefits, possibly attributable to differences in study patient clinical characteristics and degree of GLN depletion within and between studies, as well as the dose of parenteral GLN used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Critical illness PN de Beaux et al (14) Déchelotte et al (15) Estivariz et al (16) Fuentes-Orozco et al (18) Fuentes-Orozco et al (17) Griffiths et al (21) Ockenga et al (33) Perez-Barcena et al (36) Sahin et al (38) Wischmeyer et al (42) Subtotal (95 % CI) Total events: 104 (treatment), 136 (control) Test for heterogeneity: χ 2 12·9, df 9 (P=0·17), I 2 30·4 % Test for overall effect: Z 2·24 (P=0·03)…”
Section: Methodsmentioning
confidence: 99%
“…GLN supplementation in patients submitted to elective surgery attenuates the negative postoperative nitrogen balance, diminishing the dive in intracellular concentration of the amino acid in skeletal muscle and enhancing the synthesis of muscle protein 5,6 . Parenteral nutrition supplemented with the dipeptide alanyl-glutamine in patients in an intensive care unit is associated with a reduction in infection complications and better metabolic tolerance 7 . The effect of parenteral GLN treatment has not been assessed in the setting of palatoplasty in children.…”
Section: Introductionmentioning
confidence: 99%